Effectiveness of Oil Palm Frond Activated Carbon for Removing COD, Color and Fe from Landfill Leachate - Mohd Suffian Yusoff; Nor Hana Adam; Kameleswary Watalinggam; Hamidi Abdul Aziz; Motasem Y.D. Alazaiza (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
This study examined the applicability of oil palm frond-activated carbon (OPF-AC) as adsorbent in the treatment of landfill leachate. OPF-AC was prepared by mixing granular OPF with an aqueous solution composed of distilled water and zinc chloride (ZnCl2) at different ratios. Batch experiment studies were carried out to investigate the optimum OPF-AC dosage as well as the optimum shaking time. The optimum condition was achieved at 1.2 g of OPF-AC dosage and 50 minutes of shaking time. The highest removals of COD, color and Fe (77%, 75% and 69%, respectively) were obtained at the optimum condition. Meanwhile, the adsorption capacities were 146.93 mg/g (COD), 56.43 mg/g (color) and 0.11 mg/g (Fe). The increase in adsorbent dosage also resulted in a larger free surface area and exchangeable binding sites. However, the unsaturation of adsorption sites during the adsorption process resulted in a slight drop in removal efficiency of COD, color, and Fe. Furthermore, due to the aggregation and overcrowding of adsorbent particles, the use of a greater amount of adsorbent dosage imposed particle interactions.